GAYA BAHASA FIGURATIF DALAM ANTOLOGI PUISI UNTAIAN ASA DI MUARA KERINDUAN KARYA METROPOLY MERLIN J. LIUBANA - Mestriyani Tasekeb, Milka; Bere Nahak, Kristofel; Da Conceicao Verdial, Jose (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Humans use language as a communication tool to express ideas, main ideas, or certain intentions, whether spoken or written. Writing literary works is one of the significant functions of language. Through the use of imagination, authors create literary works of art. Literary works use figurative words (figurative speech) to convey a beautiful idea or main idea in the form of a certain meaning by the author. The author can convey a message with figurative language to evoke emotions, imagination, and enthusiasm in the reader's soul. This research aims to describe the use of figurative language in the poetry anthology Strand of Asa in Muara Kerinduan by Metropoly Merlin J. Liubana. The issue at hand concerns how figurative language styles are used in the poetry anthology “Untaian Asa di Muara Kerinduan by Metropoly Merlin J. Liubana. Additionally, the approach utilized is both descriptive and qualitative. The process of data collection involves reading, recording, classifying, and entering data into a database. This research utilizes data analysis techniques such as data reduction, data presentation, concluding, and verification. In the research, it was found that hyperbole 3 data, simile 1 0 data, allegory 1 data, personification 21 data, metaphor 2 data, synecdoche 1 data, and hypallage 1 data in the form of comparative figurative language, in addition, the figure of speech known as affirmation involves the repetition of three data points. The figure of speech of satire consists of a single satire, and the figure of speech of contradiction consists of litotes of one word. Furthermore, the personification figure of speech is the dominant form of figurative language, which is used to describe the speaker's character and actions, to make the poem livelier and clearer, it needs to include more characters.